A tetra-functional polymeric rosin uv resin, its preparation method and application

CN122831809APending Publication Date: 2026-09-29QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611003979.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

但目前针对聚合松香的光固化功能化改性研究相对匮乏,现有合成工艺难以在聚合松香分子骨架上高效接枝多个丙烯酰氧基活性基团,已公开的聚合松香基UV树脂普遍存在官能度偏低、合成步骤冗长、接枝效率不高的问题,无法同时实现高生物基含量与高交联密度的兼顾,难以满足高性能光固化材料的应用需求,也制约了松香资源的高值化利用水平

Benefits of technology

本发明合理利用聚合松香分子结构中的两个羧基(-COOH)活性基团,合成了一种四官能度的聚合松香UV树脂,合成方法简单、安全,反应时间短,易于控制,成本低。在紫外光照射下,合成的四官能度聚合松香UV树脂与稀释剂混合后在短时间内即可形成性能良好的光固化材料。UV树脂的官能度是指在发生缩合反应时,UV树脂单体分子中能够实际参与化学反应的活性基团的数目。由于多官能度树脂每个分子可以参与更多的交联反应,因此在相同的光照条件下,其固化速度比单官能度UV树脂更快,并且在固化过程中可以形成更密集的交联网络,这会导致固化产物更坚硬、更耐磨。因此,本发明的四官能度聚合松香UV树脂光固化后可形成机械性能良好的聚合材料。另外,本发明的光固化材料结构中还含有聚合松香刚性六环菲骨架单元结构,进一步赋予了光固化材料更良好的性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122831809A_ABST
    Figure CN122831809A_ABST
Patent Text Reader

Abstract

The application provides a tetrafunctional polymerized rosin UV resin and a preparation method and application thereof, and belongs to the technical field of high polymer materials. The preparation method of the tetrafunctional polymerized rosin UV resin is as follows: polymerized rosin is dissolved in N,N-dimethylformamide solvent, then dimethyl glyceryl acrylate, a polymerization inhibitor hydroquinone and a catalyst zinc oxide are added, and the reaction is carried out under microwave-assisted heating to obtain the tetrafunctional polymerized rosin UV resin. The tetrafunctional polymerized rosin UV resin is mixed with a diluent and a photoinitiator and subjected to ultraviolet irradiation to obtain a polymerized rosin-based photocuring material. The preparation method is simple and low in energy consumption, the mechanical property, thermal stability, water resistance and acid and alkali resistance of the photocuring material are improved, the tetrafunctional polymerized rosin UV resin can be applied to the fields of UV ink, UV coating or 3D light printing and the like, and the high-value utilization of rosin is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, and particularly relates to a tetrafunctional polymeric rosin UV resin, its preparation method and application. Background Technology

[0002] Ultraviolet (UV) curing technology is an advanced surface treatment technology characterized by high efficiency, energy saving, economy, good adaptability, and environmental friendliness, and has seen rapid development and application in recent years. UV-curable coatings refer to coating technologies that utilize ultraviolet light to excite photoinitiators, promoting free radical or cationic polymerization and cross-linking in a short time, rapidly curing liquid materials into solid coatings. This technology does not contain volatile organic solvents, is environmentally friendly, and can cure into films in a short time, resulting in high production efficiency and multiple advantages such as reduced environmental impact, increased production efficiency, and lower energy costs. Currently, commercially available photocurable oligomers, such as epoxy acrylates, polyurethane acrylates, and polyester acrylates, rely heavily on non-renewable petroleum resources for their raw materials. With the increasing depletion of petroleum resources and the aggravation of environmental problems, the development of bio-based photocurable materials based on renewable resources has become an important research direction in this field.

[0003] Rosin, as an abundant and inexpensive natural biomass resource, has a unique hydrogenated phenanthrene ring rigid structure as its main component, rosin acid, which provides excellent rigidity, thermal stability, and hydrophobicity for polymer materials, making it an ideal raw material for developing bio-based photocurable resins. However, the direct use of ordinary rosin (or hydrogenated rosin) in high-performance photocurable systems is limited due to its low molecular weight, easy oxidation of conjugated double bonds, and poor thermal stability and compatibility. Current research on the modification of rosin-based photocurable resins mainly involves grafting acrylate active groups onto the rosin backbone through esterification, epoxy ring-opening, and other reactions. However, most modified products have monofunctional or bifunctional structures, resulting in low crosslinking density after curing. This fails to fully utilize the rigidity-enhancing effect of the hydrogenated phenanthrene ring, and the physical and mechanical properties, water resistance, and acid and alkali resistance of the cured film are insufficient to meet the requirements of high-performance industrial applications. To improve resin functionality, some existing technologies require the introduction of a large number of petroleum-based multifunctional intermediates, which not only increases the synthesis steps and production costs, but also significantly reduces the bio-based content of the resin, weakening the environmentally friendly properties of biomass materials.

[0004] Polymerized rosin is a modified product obtained by cationic catalytic polymerization of rosin, with dimerized rosin as the main component. Compared with ordinary rosin, it has a higher softening point, significantly improved thermal stability and antioxidant properties, as well as a lighter color and lower acid value. Furthermore, it has a higher density of hydrogenated phenanthrene rings per molecule, making it more promising for the preparation of high-performance bio-based photocurable resins. However, current research on the photocurable functionalization modification of polymerized rosin is relatively scarce. Existing synthesis processes struggle to efficiently graft multiple acryloyloxy active groups onto the polymerized rosin molecular backbone. Publicly available polymerized rosin-based UV resins generally suffer from low functionality, lengthy synthesis steps, and low grafting efficiency, failing to simultaneously achieve high bio-based content and high crosslinking density. This makes it difficult to meet the application requirements of high-performance photocurable materials and also restricts the high-value utilization of rosin resources.

[0005] Therefore, providing a tetrafunctional polymeric rosin UV resin with high functionality, simple synthesis process, high bio-based content, and excellent comprehensive performance of cured products, as well as its preparation method, is of great significance for expanding the high-value utilization pathways of rosin and promoting the industrial application of bio-based photocurable materials. Summary of the Invention

[0006] To address the aforementioned problems in the prior art, this invention provides a tetrafunctional polymeric rosin UV resin, its preparation method, and its applications. This invention uses polymeric rosin, a polymerized product of renewable rosin, as raw material to synthesize a tetrafunctional polymeric rosin UV resin. Then, a photoinitiator, Darocure 1173, is added for photocuring at room temperature to form a photocurable material. The preparation process is simple and energy-efficient, improving the physical and mechanical properties, water resistance, and acid and alkali resistance of the photocurable material. It can be applied in UV coatings, inks, 3D printing, and adhesives, significantly enhancing the high-value utilization of rosin.

[0007] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of the present invention: This invention provides a tetrafunctional polymeric rosin UV resin, the structural formula of which is shown in Formula I:

[0008] Formula I.

[0009] The second technical solution of the present invention: The present invention also provides a method for preparing the aforementioned tetrafunctional polymerized rosin UV resin, comprising the following steps: Polymerized rosin was dissolved in N,N-dimethylformamide (DMF) solvent, and then glyceryl dimethacrylate, polymerization inhibitor and catalyst were added. The reaction was carried out under microwave-assisted heating to obtain the tetrafunctional polymerized rosin UV resin.

[0010] Furthermore, the polymerized rosin has dimerized rosin as its main component, a softening point of 140-145℃, and an acid value of 140mgKOH / g.

[0011] Furthermore, the polymerization inhibitor is hydroquinone; The catalyst is zinc oxide.

[0012] Beneficial effects: Esterification reactions usually use inorganic liquid acids such as concentrated sulfuric acid and concentrated phosphoric acid as catalysts, which result in many side reactions and waste acid pollution, and the post-treatment neutralization is troublesome. This invention selects inorganic solid acid zinc oxide as catalyst, which is easy to separate and produces no waste acid.

[0013] Furthermore, the molar ratio of the polymerized rosin to glyceryl dimethacrylate is 1:(3-4). The mixing ratio of the polymerized rosin to N,N-dimethylformamide solvent is 1 g: 3 mL; The amount of catalyst added is 1%-2% of the total mass of the polymerized rosin and glyceryl dimethacrylate; The amount of the polymerization inhibitor added is 0.1%-0.2% of the total mass of the polymerized rosin and glyceryl dimethacrylate.

[0014] Furthermore, the microwave-assisted heating temperature is 100-120℃, the reaction time is 30-60 min, and the microwave power is 480-600 W, preferably 600 W. This invention employs microwave heating, which provides mild reaction conditions, short reaction time, a simple and safe synthesis method, is easy to control, and has low cost.

[0015] Beneficial effects: Microwave radiation heating is a technology for achieving efficient and highly selective synthesis. Through precise energy transfer at the molecular level, homogenization of high-viscosity systems, optimization of reaction kinetics, and effective suppression of side reactions, it ensures the efficient and reproducible synthesis of products with well-defined structures, complete functionality, and excellent performance. Surpassing conventional heating methods, it achieves precise energy matching with the reaction system and mechanism, and efficient coupling with polar media to achieve instantaneous and uniform heating of the reaction system, significantly reducing reaction time.

[0016] Furthermore, in order to improve reaction efficiency and product purity, the reaction ends when the carboxyl groups of the polymerized rosin and the hydroxyl groups of the dimethacrylate have completely reacted, i.e., when the acid value of the product no longer changes.

[0017] The third technical solution of the present invention: The present invention also provides a polymeric rosin-based photocurable material, which is prepared using the aforementioned tetrafunctional polymeric rosin UV resin.

[0018] Furthermore, the preparation method of the polymeric rosin-based photocurable material includes the following steps: The tetrafunctional polymeric rosin UV resin, diluent, and photoinitiator are mixed evenly and then irradiated with ultraviolet light to obtain the polymeric rosin-based photocurable material.

[0019] Furthermore, the diluent includes any one of hydroxyethyl methacrylate, 4-acryloylmorpholine, polyethylene glycol diacrylate, 1,6-hexanediol diacrylate, 2-hydroxyethyl acrylate, and tripropylene glycol diacrylate, preferably hydroxyethyl methacrylate, which is more conducive to improving the mechanical properties of the photocurable material. The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone (Darocure1173).

[0020] Furthermore, the mass ratio of the tetrafunctional polymerized rosin UV resin to the diluent is 1:(1-4). The photoinitiator is 5%-12% of the tetrafunctional polymerized rosin UV resin, preferably 8%-10%.

[0021] Furthermore, applying the mixed photocuring solution to a tinplate or polypropylene plastic sheet before UV irradiation results in higher adhesion on the tinplate and polypropylene plastic sheet.

[0022] Furthermore, the intensity of the ultraviolet light irradiation is 635 mJ / cm². 2 The irradiation time is 15-30 seconds.

[0023] The fourth technical solution of the present invention: The present invention also provides an application of the polymeric rosin-based photocurable material in UV coatings, inks, 3D printing and adhesives.

[0024] The beneficial effects of this invention compared to the prior art are as follows: This invention rationally utilizes the two carboxyl (-COOH) active groups in the molecular structure of polymeric rosin to synthesize a tetrafunctional polymeric rosin UV resin. The synthesis method is simple, safe, has a short reaction time, is easy to control, and is low in cost. Under ultraviolet light irradiation, the synthesized tetrafunctional polymeric rosin UV resin, when mixed with a diluent, can form a high-performance photocurable material in a short time. The functionality of a UV resin refers to the number of active groups in the UV resin monomer molecule that can actually participate in the chemical reaction during condensation. Because each molecule of a multifunctional resin can participate in more cross-linking reactions, its curing speed is faster than that of a monofunctional UV resin under the same light conditions, and a denser cross-linking network can be formed during the curing process, resulting in a harder and more wear-resistant cured product. Therefore, the tetrafunctional polymeric rosin UV resin of this invention can form a polymeric material with good mechanical properties after photocuring. In addition, the photocurable material structure of this invention also contains a rigid hexagonal phenanthrene skeleton unit structure of polymeric rosin, further endowing the photocurable material with better properties.

[0025] In existing technologies, the diluent monomer typically only reaches 6%-8% of the UV resin mass, with a maximum of 10%. If the diluent content is continuously increased, it leads to a decrease in the strength and adhesion of the UV-cured resin, failing to meet usage requirements. Conversely, insufficient diluent usage results in poor operability and increased operational difficulty, thus affecting the quality of the UV-cured material. The diluent of this invention can reach up to 400% of the UV resin mass, and its content can be controlled within the range of 100%-400%. Various properties of the UV-cured material can be adjusted according to actual application needs because the UV resin of this invention has multiple functionalities.

[0026] The tetrafunctional polymeric rosin UV resin of this invention is a bio-based resin that can replace non-renewable petroleum-based resins, meeting the requirements of green chemistry development. Furthermore, the polymeric rosin-based UV-curable material of this invention possesses excellent physical and mechanical properties (high thermal stability, low shrinkage, strong adhesion and tensile strength, etc.), as well as good water resistance and acid and alkali resistance. Therefore, it has wide applications in UV coatings, inks, 3D printing, adhesives, and other fields, greatly improving the high-value utilization of renewable rosin resources. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 The infrared spectrum of the tetrafunctional polymeric rosin UV resin prepared in Example 1 of this invention; Figure 2 Thermogravimetric analysis diagram of the polymeric rosin-based photocurable material prepared in Application Example 2 of this invention; Figure 3 The tensile property curves of polymeric rosin-based photocurable materials prepared by different mass ratios of tetrafunctional polymeric rosin UV resin to diluent in this invention are shown. Figure 4 This is a gel permeation chromatogram of the polymeric rosin-based photocurable material prepared in Application Example 2 of this invention; Figure 5 The image shows the water droplet contact angle test result of the polymeric rosin-based photocurable material prepared in Application Example 2 of this invention. Detailed Implementation

[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0030] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0031] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0032] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0033] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0034] The polymeric rosin described in the following embodiments of the present invention was purchased from Yunfu Shengda Rosin Chemical Plant Co., Ltd., with a softening point of 140-145℃ and an acid value of 140 mgKOH / g.

[0035] Example 1 A method for preparing a tetrafunctional polymeric rosin UV resin includes the following steps: 10 g of polymerized rosin was dissolved in 30 mL of DMF solvent. Then, 13.23 g of glyceryl dimethacrylate, 0.04 g of hydroquinone, and 0.24 g of zinc oxide were added together with the polymerized rosin DMF solution into a reactor. The reaction was carried out under microwave-assisted heating at a power of 600 W, a reaction temperature of 110 °C, and a reaction time of 1 h. After the reaction was completed, the zinc oxide was removed by filtration. Then, DMF and unreacted raw materials were removed by rotary evaporation to obtain a tetrafunctional polymerized rosin UV resin. The infrared spectra of the polymerized rosin and the prepared tetrafunctional polymerized rosin UV resin are shown below. Figure 1 As shown, through Figure 1 It can be seen that in the infrared spectrum of the tetrafunctional polymerized rosin UV resin, 1161.85 cm⁻¹ -1 The presence of a distinct stretching vibration peak of the ester group COC indicates that the polymerized rosin has successfully undergone esterification.

[0036] The tetrafunctional polymerized rosin UV resin prepared in Example 1 was tested, and the results showed that the acid value was 8.3 mgKOH / g and the esterification rate reached 94.07%.

[0037] Example 2 A method for preparing a tetrafunctional polymeric rosin UV resin includes the following steps: 10 g of polymerized rosin was dissolved in 30 mL of DMF solvent, and then 15.09 g of glyceryl dimethacrylate, 0.04 g of hydroquinone and 0.26 g of zinc oxide were added together with the DMF solution of polymerized rosin into a reactor. The reaction was carried out under microwave-assisted heating with a microwave power of 600 W, a reaction temperature of 110 °C and a reaction time of 1 h. After the reaction was completed, the zinc oxide was removed by filtration, and then the DMF and unreacted raw materials were removed by rotary evaporation to obtain tetrafunctional polymerized rosin UV resin.

[0038] The tetrafunctional polymerized rosin UV resin prepared in Example 2 was tested, and the results showed that the acid value was 15.7 mgKOH / g and the esterification rate reached 88.79%.

[0039] Example 3 A method for preparing a tetrafunctional polymeric rosin UV resin includes the following steps: 10 g of polymerized rosin was dissolved in 30 mL of DMF solvent, and then 13.23 g of glyceryl dimethacrylate, 0.04 g of hydroquinone and 0.24 g of zinc oxide were added together with the DMF solution of polymerized rosin into a reactor. The reaction was carried out under microwave-assisted heating with a microwave power of 600 W, a reaction temperature of 110 °C and a reaction time of 45 min. After the reaction was completed, the zinc oxide was removed by filtration, and then the DMF and unreacted raw materials were removed by rotary evaporation to obtain tetrafunctional polymerized rosin UV resin.

[0040] The tetrafunctional polymerized rosin UV resin prepared in Example 3 was tested, and the results showed that the acid value was 13.47 mgKOH / g and the esterification rate reached 90.37%.

[0041] Example 4 A method for preparing a tetrafunctional polymeric rosin UV resin includes the following steps: 10 g of polymerized rosin was dissolved in 30 mL of DMF solvent, and then 13.23 g of glyceryl dimethacrylate, 0.04 g of hydroquinone and 0.24 g of zinc oxide were added together with the DMF solution of polymerized rosin into a reactor. The reaction was carried out under microwave-assisted heating with a microwave power of 600 W, a reaction temperature of 125 °C and a reaction time of 1 h. After the reaction was completed, the zinc oxide was removed by filtration, and then the DMF and unreacted raw materials were removed by rotary evaporation to obtain tetrafunctional polymerized rosin UV resin.

[0042] The tetrafunctional polymerized rosin UV resin prepared in Example 4 was tested, and the results showed that the acid value was 18.07 mgKOH / g and the esterification rate reached 87.09%.

[0043] Comparative Example 1 A method for preparing a photocurable resin includes the following steps: 10 g of polymerized rosin was heated to a molten state, and the temperature was raised to 230°C. 13.23 g of glyceryl dimethacrylate and 0.04 g of hydroquinone were mixed and added dropwise to the molten polymerized rosin, along with 0.24 g of zinc oxide. Nitrogen gas was introduced, and the mixture was mechanically stirred to initiate the reaction. The acid value was measured every hour. After 4 hours, the acid value remained unchanged, indicating the end of the reaction. A large amount of insoluble matter was observed. This is because under conventional heating conditions, esterification requires high temperatures, which readily trigger the self-polymerization reaction of the polymerized rosin UV resin, thus reducing the yield of the polymerized rosin UV resin itself. The reaction product was dissolved in toluene, and the insoluble matter was removed by filtration. The UV-curable resin was then obtained by rotary evaporation.

[0044] The photocurable resin prepared in Comparative Example 1 was tested, and the results showed that the acid value was 18.3 mgKOH / g and the esterification rate was 86.92%. Although Comparative Example 1 underwent esterification, it also underwent self-polymerization after esterification.

[0045] Application Example 1 A method for preparing a polymeric rosin-based photocurable material includes the following steps: 1 g of photoinitiator Darocure 1173 was added to 10 g of the tetrafunctional polymerized rosin UV resin prepared in Example 1, followed by the addition of 10 g of hydroxyethyl methacrylate. The mixture was then thoroughly mixed under ultrasonic vibration to obtain a photocurable solution. This solution was then uniformly coated onto a tinplate or polypropylene plastic sheet using a 100 μm wet film preparation device to form a liquid film with a strength of 635 mJ / cm². 2 The material was cured under ultraviolet light for 15 seconds to obtain a polymeric rosin-based UV-curable material. The material has a smooth and transparent surface and an adhesion rating of 0 on both tinplate and polypropylene plastic sheets. The lower the rating, the stronger the adhesion.

[0046] The polymeric rosin-based photocurable material prepared according to Example 1 was tested for pencil hardness, and its hardness reached 5H. The prepared photocurable solution was injected into a polytetrafluoroethylene mold, and after photocuring under ultraviolet light, a uniaxial tensile test was performed, showing a tensile strength of 2.98 MPa.

[0047] Application Example 2 A method for preparing a polymeric rosin-based photocurable material includes the following steps: 1 g of photoinitiator Darocure 1173 was added to 10 g of the tetrafunctional polymerized rosin UV resin prepared in Example 1, followed by the addition of 35 g of hydroxyethyl methacrylate. The mixture was then thoroughly mixed under ultrasonic vibration to obtain a photocurable solution. This solution was then uniformly coated onto a tinplate or polypropylene plastic sheet using a 100 μm wet film preparation device to form a liquid film with a strength of 635 mJ / cm². 2 The material was cured under ultraviolet light for 15 seconds to obtain a polymeric rosin-based UV-curable material. The material has a smooth and transparent surface and an adhesion rating of 0 on both tinplate and polypropylene plastic sheets. The lower the rating, the stronger the adhesion.

[0048] The polymeric rosin-based photocurable material prepared according to Example 2 was tested for pencil hardness, and its hardness reached 5H. After the prepared photocurable solution was injected into a polytetrafluoroethylene mold and photocured under ultraviolet light, a uniaxial tensile test was performed, and the tensile strength reached 19.44 MPa.

[0049] Thermogravimetric analysis was performed on the polymeric rosin-based photocurable material prepared in accordance with example 2, and the results are as follows: Figure 2 As shown, through Figure 2 As can be seen, in the 0-200℃ range, the curve is almost horizontal, the mass of the photocurable material remains 100%, there is no significant weight loss, and the material is thermally stable. After 200℃, the curve begins to slope downwards significantly, the mass of the photocurable material continues to decrease, indicating that the molecular chains begin to undergo thermal decomposition and volatilization, officially entering the thermal decomposition stage. The 400-500℃ range is the rapid and violent decomposition zone, with the largest weight loss rate. After 500℃, the residue tends to stabilize. Therefore, the thermal decomposition start temperature of the photocurable material prepared in this invention is 200℃, indicating that it has high thermal stability.

[0050] Application Example 3 A method for preparing a polymeric rosin-based photocurable material includes the following steps: 1 g of photoinitiator Darocure 1173 was added to 10 g of the tetrafunctional polymerized rosin UV resin prepared in Example 1, followed by 10 g of 4-acryloylmorpholine. The mixture was then stirred evenly under ultrasonic vibration to obtain a photocurable solution. The photocurable solution was then uniformly coated onto a tinplate or polypropylene plastic sheet using a 100 μm wet film preparation device to form a liquid film. The film was then heated to a strength of 635 mJ / cm². 2 The material was cured under ultraviolet light for 15 seconds to obtain a polymeric rosin-based UV-curable material. The material has a smooth and transparent surface and an adhesion rating of 5 on tinplate and 0 on polypropylene plastic sheet. The lower the rating, the stronger the adhesion.

[0051] The polymeric rosin-based photocurable material prepared according to Example 3 was tested for pencil hardness, and its hardness reached HB. The prepared photocurable solution was injected into a polytetrafluoroethylene mold, and after photocuring under ultraviolet light, a uniaxial tensile test was performed, showing a tensile strength of 2.91 MPa.

[0052] Application Example 4 A method for preparing a polymeric rosin-based photocurable material includes the following steps: 1 g of photoinitiator Darocure 1173 was added to 10 g of the tetrafunctional polymeric rosin UV resin prepared in Example 1, followed by 10 g of polyethylene glycol diacrylate. The mixture was then stirred evenly under ultrasonic vibration to obtain a photocurable solution. The photocurable solution was then uniformly coated onto a tinplate or polypropylene plastic sheet using a 100 μm wet film preparation device to form a liquid film with a strength of 635 mJ / cm². 2The material was cured under ultraviolet light for 15 seconds to obtain a polymeric rosin-based UV-curable material. The material has a smooth and transparent surface and an adhesion rating of 2 on tinplate and 5 on polypropylene plastic sheet. The lower the rating, the stronger the adhesion.

[0053] The polymeric rosin-based photocurable material prepared according to Example 4 was tested for pencil hardness, and its hardness reached HB. The prepared photocurable solution was injected into a polytetrafluoroethylene mold, and after photocuring under ultraviolet light, a uniaxial tensile test was performed, showing a tensile strength of 2.27 MPa.

[0054] Application Example 5 The effect of the mass ratio of tetrafunctional polymeric rosin UV resin to diluent on the mechanical tensile properties of polymeric rosin-based photocurable materials One g of photoinitiator Darocure 1173 was added to 10 g of the tetrafunctional polymeric rosin UV resin prepared in Example 1. Then, 10 g, 20 g, 30 g, 35 g, and 40 g of hydroxyethyl methacrylate (the mass ratio of tetrafunctional polymeric rosin UV resin to diluent was 1:1, 1:2, 1:3, 1:3.5, and 1:4, respectively) were added. The mixture was then thoroughly mixed under ultrasonic vibration to obtain five photocurable solutions. The prepared photocurable solutions were injected into polytetrafluoroethylene molds and photocured under a UV lamp with an irradiation intensity of 635 mJ / cm². 2 Five polymeric rosin-based photocurable materials were obtained after irradiation for 15 seconds. Uniaxial tensile tests were then performed on each material, and the results are as follows: Figure 3 As shown, through Figure 3 It can be seen that the maximum tensile strength of the prepared polymeric rosin-based photocurable material can reach 19.44 MPa, and the maximum elongation at break can reach 53.07%.

[0055] Performance testing 1. The polymeric rosin-based photocurable material prepared according to example 2 was characterized by gel permeation chromatography. The test results are as follows: Figure 4 As shown, through Figure 4 It can be seen that the peak-average molecular weight (M) of this material n The weight-average molecular weight (M) is 29760. w The molecular weight is 33313, and the high molecular weight is due to the high functionality of the polymerized rosin-based UV resin prepolymer. During the photocuring process, a three-dimensional network skeleton with extremely high crosslinking density can be constructed, thereby endowing the material with excellent mechanical strength, solvent resistance and thermal stability, which are the key properties required for photocuring applications.

[0056] 2. Water resistance test The polymeric rosin-based photocurable material prepared in Application Example 2 was cut into 2 cm × 2 cm pieces, weighed, and then immersed in deionized water at room temperature for 48 h. After immersion, the material was removed, the surface solution was wiped dry, and the material was weighed again to compare the mass before and after immersion. The calculated water absorption rate of the polymeric rosin-based photocurable material was 0.76%. The water droplet contact angle of the photocurable material was measured, and the results are as follows: Figure 5 As shown, through Figure 5 As can be seen, the water droplets on the coating surface are full, raised, and nearly spherical, with no obvious spreading or wetting phenomenon. According to software fitting calculation, the water contact angle of this photocurable coating can reach 117.74°. The contact angle value is much greater than the 90° hydrophilic-hydrophobic critical threshold, proving that the photocurable material prepared by this invention has low surface energy, excellent hydrophobicity, and can effectively block water penetration, thereby improving the coating's resistance to water and acid and alkali corrosion.

[0057] 3. Acid and alkali resistance test The polymeric rosin-based photocurable material prepared in Application Example 2 was cut into 2 cm × 2 cm pieces, weighed, and then immersed in 10 wt.% H₂SO₄ solution and 5 wt.% NaOH solution at room temperature for 48 h, respectively. After immersion, the materials were removed, the surface solution was wiped dry, and the materials were weighed again to compare the mass before and after immersion. Calculations showed that the water absorption rates of the polymeric rosin-based photocurable material were 0.81% and 0.76%, respectively, indicating that the photocurable material has good acid and alkali resistance.

[0058] 4. Shrinkage test For the polymeric rosin-based UV-curable material corresponding to Example 2, the standard length of the liquid resin in the mold before curing and the actual length of the sample after curing and demolding were measured. Calculations showed that the shrinkage rate of the polymeric rosin-based UV-curable material was 0.3%, indicating that the UV-curable material has an extremely low shrinkage rate.

[0059] 5. Properties of UV-curable materials prepared with different UV resins Weigh out 10 g each of difunctional rosin-based photocurable resin (R-GDMA), difunctional polymeric rosin-based photocurable resin (PR-HEA), tetrafunctional polymeric rosin-based photocurable resin (PR-GDMA), bisphenol A glycerol dimethacrylate (Bis-GMA), and polyurethane acrylate (PUA). Then add 1 g of photoinitiator Darocure 1173 to each, followed by 35 g of hydroxyethyl methacrylate. Mix thoroughly under ultrasonic vibration to obtain a photocurable solution. Use a 100 μm wet film preparation device to evenly coat the photocurable solution onto a tinplate or polypropylene plastic sheet to form a liquid film. The film is then heated to a strength of 635 mJ / cm². 2 The material was cured by irradiation under ultraviolet light to obtain a photocurable material. The performance of the photocurable material was tested, and the results are shown in Table 1.

[0060] Table 1

[0061] As shown in Table 1, the UV-curable material formed by the tetrafunctional polymerized rosin UV resin prepared in this invention has superior adhesion, hardness, acid and alkali resistance, water resistance and tensile properties compared to UV-curable materials prepared by other resins. Moreover, the curing time is short, which shortens the preparation time of the UV-curable material.

[0062] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A tetrafunctional polymeric rosin UV resin, characterized in that, The structural formula of the tetrafunctional polymeric rosin UV resin is shown in Formula I: Formula I.

2. A method for preparing the tetrafunctional polymeric rosin UV resin as described in claim 1, characterized in that, Includes the following steps: Polymerized rosin was dissolved in N,N-dimethylformamide solvent, and then glyceryl dimethacrylate, polymerization inhibitor and catalyst were added. The reaction was carried out under microwave-assisted heating to obtain the tetrafunctional polymerized rosin UV resin.

3. The method for preparing the tetrafunctional polymerized rosin UV resin according to claim 2, characterized in that, The polymerization inhibitor is hydroquinone; The catalyst is zinc oxide; The molar ratio of the polymerized rosin to glyceryl dimethacrylate is 1:(3-4). The mixture of the polymerized rosin and N,N-dimethylformamide solvent is 1 g: 3 mL; The amount of catalyst added is 1%-2% of the total mass of the polymerized rosin and glyceryl dimethacrylate; The amount of the polymerization inhibitor added is 0.1%-0.2% of the total mass of the polymerized rosin and glyceryl dimethacrylate.

4. The method for preparing the tetrafunctional polymerized rosin UV resin according to claim 2, characterized in that, The microwave-assisted heating temperature is 100-120℃, the reaction time is 30-60 min, and the microwave power is 480-600 W.

5. A polymeric rosin-based photocurable material, characterized in that, It was prepared using the tetrafunctional polymerized rosin UV resin described in claim 1.

6. The polymeric rosin-based photocurable material according to claim 5, characterized in that, The preparation method of the polymeric rosin-based photocurable material includes the following steps: The tetrafunctional polymeric rosin UV resin, diluent, and photoinitiator are mixed evenly and then irradiated with ultraviolet light to obtain the polymeric rosin-based photocurable material.

7. The polymeric rosin-based photocurable material according to claim 6, characterized in that, The diluent includes any one of hydroxyethyl methacrylate, 4-acryloylmorpholine, polyethylene glycol diacrylate, 1,6-hexanediol diacrylate, 2-hydroxyethyl acrylate, and tripropylene glycol diacrylate. The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.

8. The method for preparing the polymeric rosin-based photocurable material according to claim 6, characterized in that, The mass ratio of the tetrafunctional polymerized rosin UV resin to the diluent is 1:(1-4). The mass of the photoinitiator is 5%-12% of the tetrafunctional polymerized rosin UV resin.

9. The method for preparing the polymeric rosin-based photocurable material according to claim 6, characterized in that, The intensity of the ultraviolet light irradiation was 635 mJ / cm. 2 The irradiation time is 15-30 seconds.

10. The application of the polymeric rosin-based photocurable material as described in claim 5 in UV coatings, inks, 3D printing, and adhesives.